Gang glocalization: How the global mediascape creates and shapes local gang realities. (March 2019) - Van Hellemont, Elke; Densley, James A
This article introduces the concept of 'gang glocalization' to capture the processes by which global media myths and conventions create and shape local gang realities. The different stages of gang glocalization, and the motives to engage in this process, are examined by comparison of two empirical cases – Congolese gangs in Brussels and Afro-Caribbean gangs in London. This multi-sited ethnography finds that youth use fiction and imagination in order to create individual and collective gang identities. Police and political action against gangs is then informed by the same fiction and imagination, resulting in new gang realities based not on what is real. We find that mythmaking is an essential aspect of gangs – without the myth there is no gang – and that imagination is at the core of some of its most harmful activities, namely spectacular symbolic violence. This is an update on Thrasher's (1927) old themes. The driving forces behind gang glocalization are emotions and desires tied to lived experiences of social and cultural exclusion. Implications for research and practice follow.